Teaching strategies to develop transversal skills using Web 2.0 - Tulcán Benavides, Fabián Laureano; López Cevallos, Franklin Ernesto (SATHIRI, 2025)
In the city of Tulcán, the San Antonio de Padua Educational Unit offers training at three educational levels: Higher Basic, Unified Baccalaureate and Technical in Accounting and Administration, where flexibility to adapt to the changes demanded by today’s society implies assuming transformations in methodologies. didactics applied by teachers, in relation to the design of pedagogical activities using digital tools in training processes. The starting point was the evident use of technological tools by teachers in times of pandemic as a means in and for teaching. This allowed the analysis of a new training paradigm incorporating online Web 2.0 tools in the design of new teaching strategies for the development of transversal skills. The mixed methodology used in the research was carried out from the diagnosis of the problem through surveys applied to high school students and educators, regarding knowledge, mastery and use of Web 2.0 in academic activities. The analysis of results allowed us to propose the pedagogical proposal that directed efforts in the development of meaningful educational environments, using didactic strategies such as the “WebQuest” during classroom work and “Remembering knowledge” as an alternative for diagnostic evaluation; alternatives that require the search for information, research, communication, creativity, collaboration, construction, as axes that promote and motivate learning. It is concluded that the teaching strategies designed and used in a planned manner, inserting technological tools, strengthen the development of transversal competencies in students, improve teaching work and contribute to the comprehensive training process.